Factor affecting university undergraduates students perception’s toward career enhancement in hospitality industry: a case of UiTM Penang/ Mohd Zool Fadli Ibrahim - Ibrahim, Mohd Zool Fadli; Mohd Saber, Joesri; Raja Mustapha, Raja Iskandar Putera; Othman, Najikha; Salim, Azlan (Universiti Teknologi Mara Cawangan Pulau Pinang, 2020)
The hospitality industry requires skilled workers in the restaurant, hotel and lodging sector in order to perform specific and unique tasks such as serving food, bed-making, turn down services and many more. Being an industry that is labor intensive, hospitality establishments strive to attract potential workers, especially fresh graduates to join them. Fresh graduates who are knowledgeable, committed, motivated are sought after by the industry but due to a number of factors, most graduates are not keen to join the hospitality industry. One of the factors that influenced their perception of the industry is their very own experience while going through their practical training. The difference between their expectation of the industry prior to the practical training and their real experience during it is too different thus altering their perception or image of the industry. Therefore this study was conducted to examine the factors affecting the undergraduates’ perception towards the industry in the case of students from the Faculty of Hotel and Tourism Management, UiTM Penang. The findings indicated that the nature of work and social status are factors the affects the perception of the undergraduates.